Modeling Markets Analyzing Marketing Phenomena and Improving Marketing Decision Making - Leeflang, Peter S.H.; Wieringa, Jaap E.; Bijmolt, Tammo H.A.; Pauwels, Koen H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
This book is about how models can be developed to represent demand and supply on markets, where the emphasis is on demand models. Its primary focus is on models that can be used by managers to support marketing decisions. The market environment is changing rapidly and constantly. With the introduction of scanner equipment in retail outlets, the use of hand scan panels, and the data explosion caused by the Internet, the opportunity to obtain meaningful estimates of demand functions has vastly improved. Models that provide information about the sensitivity of market behavior to marketing activities such as advertising, pricing, promotions and distribution are now routinely used by managers for the identification of changes in marketing programs that can improve brand performance. In today$1 (Bs environment of information overload, the challenge is to make sense of the data that is being provided globally, in real time, from thousands of sources. Modeling Markets presents a comprehensive overview of the tools and methodologies that managers can use in decision making. It has long been known that even simple models outperform judgments in predicting outcomes in a wide variety of contexts. More complex models potentially provide insights about structural relations not available from casual observations. Although marketing models are now widely accepted, the quality of the marketing decisions is critically dependent upon the quality of the models on which those decisions are based. In this book, the authors present a wealth of insights developed at the forefront of the field, covering all key aspects of specification, estimation, validation and use of models. Many current insights and innovations in quantitative marketing are presented. Throughout the book, the authors provide examples and illustrations. This book will be of interest to researchers, analysts, managers and students who want to understand, develop or use models of marketing phenomena.s
Building models for markets -- Model specification -- Data -- Estimation and testing -- Validation and testing -- Re-estimation: introduction to more advanced estimation methods -- Examples of models for aggregate demand -- Individual demand models -- Examples of database marketing models -- Use: implementation issues -- Appendix A: Matrix algebra.
Keywords: Economics; Industrial management; Marketing; Operations research; Economics/Management Science; Marketing; Management/Business for Professionals; Operation Research/Decision Theory